Study on reaction behaviors and mechanisms of rutile TiO2 with different carbon addition in fluidized chlorination - Fan Yang; Liangying Wen; Dong Yue; Yan Zhao; Qin Peng; Meilong Hu; Zhongqing Yang (Journal of Materials Research and Technology, 2022)
The fluidized carbochlorination behaviors of TiO2 and C with different proportions were compared and analyzed experimentally. On the basis of first-principles calculations, the mechanisms of rutile TiO2 with carbon chlorination reaction were studied, and the microscopic action behaviors of adding carbon to promote the chlorination reaction of TiO2 were explored. The experimental results show that the carbochlorination rate increases with the increase of C content. When the mass ratio of TiO2 to C is 70:30, the corresponding carbochlorination rate is 79.52%. SEM and EDS images of the residue after the carbochlorination show that the TiO2 particles are cobblestone shaped, and there is peeling off on the surfaces. There are flocs on the surface, which are mainly composed of TiO2, C and other substances. The core reduction reaction of TiO2 solid particles occurs in the process of carbochlorination. The simulation results show that with the increase of the atomic proportion of C, there are more Cl atoms bonded to the surface, and the adsorption energies of the systems are lower than that of the low carbon proportions. The increase of C content is conducive to the increase of the number of the bonds and the stability of the adsorption structures.